2018
DOI: 10.1111/gec3.12404
|View full text |Cite
|
Sign up to set email alerts
|

Geo‐text data and data‐driven geospatial semantics

Abstract: Many datasets nowadays contain links between geographic locations and natural language texts. These links can be geotags, such as geotagged tweets or geotagged Wikipedia pages, in which location coordinates are explicitly attached to texts. These links can also be place mentions, such as those in news articles, travel blogs, or historical archives, in which texts are implicitly connected to the mentioned places. This kind of data is referred to as geo-text data. The availability of large amounts of geo-text da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 97 publications
0
22
0
Order By: Relevance
“…Do their movements frequently interact with each other in space and time? At an aggregate level, studies suggest that human activity space is in good agreement with the socioeconomic divisions in cities (Xu, Belyi, Bojic, & Ratti, 2017, 2018. At an individual level, it has been revealed that a large portion of the places visited by an individual usually locate within the social circles centered at his/her nearest social tie locations (Wang, Kang, Bettencourt, Liu, & Andris, 2015;Yuan & Raubal, 2016).…”
Section: Diversity In Mobility Across Socio-demographic Groupsmentioning
confidence: 92%
See 2 more Smart Citations
“…Do their movements frequently interact with each other in space and time? At an aggregate level, studies suggest that human activity space is in good agreement with the socioeconomic divisions in cities (Xu, Belyi, Bojic, & Ratti, 2017, 2018. At an individual level, it has been revealed that a large portion of the places visited by an individual usually locate within the social circles centered at his/her nearest social tie locations (Wang, Kang, Bettencourt, Liu, & Andris, 2015;Yuan & Raubal, 2016).…”
Section: Diversity In Mobility Across Socio-demographic Groupsmentioning
confidence: 92%
“…For instance, social media data that contain a large volume of texts and images are becoming a major descriptive indicator of people's cognition and emotional feelings attached to urban place in terms of sign-in, re-emergence, repetition, and aggregation (Jenkins, Croitoru, Crooks, & Stefanidis, 2016;Wu, Wang, Shi, Gao, & Liu, 2019). Machine learning and data mining methods have become mainstream tools for extracting thematic topics from textual data to quantify human activities and emotions at specific places (Gao et al, 2017;Hu, 2018;Tran, Shin, & Choi, 2018). Popular approaches include the Word2Vec model and its geo-enhanced variants (Yan, Janowicz, Mai, & Gao, 2017;Zhai et al, 2019).…”
Section: Space and Placementioning
confidence: 99%
See 1 more Smart Citation
“…Data-driven geospatial semantics refers to a bottom-up approach for eliciting geospatial knowledge from natural language texts that contain either explicit or implicit locations of places [99]. It is distinct from top-down or expert-driven approaches that extract geospatial knowledge from experts in a specific field.…”
Section: Semantic Information Elicitationmentioning
confidence: 99%
“…Geo‐text data [Hu18] contains texts and themes linked to geolocations. Examples include geo‐tagged social media, real estate information, community events, crime reports, consumer reviews, and so on.…”
Section: Introductionmentioning
confidence: 99%